Vascularized Fibula Epiphysis Transfer for Pediatric Extremity Reconstruction: A Systematic Review and Meta-analysis. Issue 3 (March 2019) - Kurlander, David E.; Shue, Shirley; Schwarz, Graham S.; Ghaznavi, Amir M.
Abstract : Background: Vascularized fibula epiphysis transfer for pediatric extremity reconstruction intends to preserve growth potential. However, few cases are reported, and outcomes are poorly characterized. Methods: Systematic review was performed through a MEDLINE search using keywords "pediatric" or "epiphyseal" and "vascularized fibula." Patients were divided into upper extremity or lower extremity groups. Functional and growth outcomes were assessed, and indications, pedicle, complications, and need for secondary surgery were recorded. Results: Twenty publications with 62 patients were included. Mean age was 5.9 years, and mean follow-up was 5.8 years. Indications included sarcoma (60%), congenital deformity (21%), trauma (13%), and infection (6%). Anterior tibial pedicle was most common (63%) and was associated with significantly improved growth outcomes compared with the peroneal pedicle (23%; P < 0.001). Fifty-three patients underwent upper extremity reconstruction, with the most common complication being fracture (35%) and most common secondary surgery flap salvage (7%). Among upper extremity patients, full function was achieved in 25% and impaired function in 75%. Full growth was observed in 63% of patients, partial growth in 31%, and no growth in 4%. Nine patients underwent lower extremity reconstruction, with the most common complication being fracture (22%) and most common secondary surgery derotational osteotomy (22%). Among lower extremity patients, full function was achieved in 44% and impaired function in 56%. Full growth was observed in 56% of patients, partial growth in 22%, and no growth in 22%. Conclusions: Vascularized fibula epiphysis transfer can accomplish full long-term growth and function. However, complications, revision surgery, and chronic impairment are common.